New tricks for old hands: How experienced primary teachers incorporate new science curricula into their practice. - Pearson, Jennifer Olwyn (Curtin University, 2002)
Primary teachers are constantly required to make changes in their teaching practice. This thesis reports on a year in the professional life of two experienced primary school teachers as they engage in implementing a new science program called Primary Investigations (Australian Academy of Science, 1994). The study examined the issues that arose as the two adapted the strategies and philosophies of the new program into their pre-existing pedagogical frameworks. The study used qualitative methods of data collection and analysis. Over ten months of participant observation several stories or narrative vignettes were created to highlight the major issues faced by the two teachers. These stories were then analysed to identify several propositions about curriculum implementation and primary science. The narrative vignettes provide descriptive accounts around several implementation issues. The two teachers experienced some problems with the supply of equipment to support their teaching and lacked the subject knowledge to identify when the equipment was inadequate. The teachers had high expectations of the teachers' resource book but a lack of science content knowledge hindered their ability to use the document with confidence. While the teachers believed that science is important for children they lacked the confidence and questioning skill to engage the students in 'science talk'. 10 teachers were able to transfer pedagogical knowledge from other disciplines 0 overcome some of the dilemmas they faced in science lessons. Both teachers displayed a strong 'ethic of care’ for the children in their class that covered gaining knowledge, behaviour towards others and safety during science lessons.There was evidence that the past experience of both teachers in their childhood and educational years had been influential in their beliefs about their interest and ability to teach science. The two teachers' personal and professional lives interacted in complex ways as they adjusted to the demands of the school year and the impact of implementing the new science program. Finally the two teachers lacked certainty in science teaching - they experienced epistemological confusion in their understanding of the nature of science. These issues lead to several implications for primary teachers of science, teacher educators, school leaders and curriculum developers.